Pemahaman Bid’ah Menurut Ulama di Desa Teluk Pulai Dalam Kecamatan Kualuh Leidong - Safrida Fitri Nasution (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2021)
The discussion about bid'ah is quite an interesting conversation, bid'ah is not a new vocabulary in the midst of the Islamic ummah. From the first heresy has always been interesting to write about. Even the scholars have discussed all aspects of the heresy. But even so, it still reaps conflict in the current era of the Islamic ummah. Because this problem is sometimes very confusing. In Islamic society, especially in Indonesia, there are different understandings of heresy. Some think that not all bid'ah is misguided. While a small number of people think that all bid'ah is heretical. Studying the problem of bid'ah in Islamic society is not easy, because it requires a definition that develops and arises around the use of the word "bid'ah". Differences in definitions can affect the different laws that are applied. Without properly defining heresy, it will only lead to legal differences, differences of opinion and cause conflict and enmity. This research was conducted in Teluk Pulai Village in Kualuh Leidong District. Attempts to study and understand the understanding of heresy according to scholars in Teluk Pulai Village in Kualuh Leidong District. The discussion of heresy will always apply in every era. The method used in this study is a qualitative method by describing the facts of the field as obtained by observation, documentation, and interviews (Interview). This type of research includes field research (Field Search) and library research (library research). Field research (Field Search) is to describe and describe the results of research more clearly regarding heresy.